The MERIS water products: Performance, current issues and potential future improvements - Bouvet, M.; Goryl, P.; Hout, J.; Antoine, David; Barker, K.; Bourg, L.; Deschamps, P.; Doerffer, R.; Fischer, J.; Mazeran, C.; Ondrusek, M.; Santer, R.; et al. (Institute of Electrical and Electronics Engineers ( IEEE ), 2009)
MERIS Level 1 and Level 2 water products will be improved in the 3rd MERIS reprocessing which is planned to take place before the end of 2009. The instrument radiometric degradation model will be updated. Improvements to the atmospheric correction in both case 1 and case 2 waters will be implemented. A vicarious adjustment strategy to remove residual biases in the Level 2 marine signals will be put in place. In addition, a cloud screening scheme with improved detection capabilities will improve the cirrus detection capability. In parallel, long term algorithmic improvements are being pursued and are partially covered by three exploratory ongoing studies. The first study addresses the limitation of the current MERIS atmospheric correction scheme in sun glint conditions. The second aims at defining an operational adjacency effect correction. The third study makes use of the ability of MERIS to measure transmission in the O2-A oxygen band to better identify and characterize clouds and aerosols.